THE EFFECT OF RELAXATION EXERCISES, AND CONCENTRATION ON SHOOTING FREE THROW RESULTS AFTER MAXIMUM TRAINING ON BASKETBALL TEAM AT INTEGRATED ISLAMIC JUNIOR HIGH SCHOOL BINA AMAL SEMARANG - Afifuddin, Taufiq; Hidayah, Taufik; Woro Kasmini Handayani, Oktia (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2020)
This study aims to analyze the effect of relaxation exercises and concentration on the results of free-throw shooting. Relaxation exercises used by researchers are progressive relaxation exercises and autogenic relaxation exercises. This experimental study uses 2x2 factorial design. A total of 20 men's basketball athletes were selected as samples with a purposive sampling technique, then divided into four experimental groups. Data analysis techniques using ANOVA. The results of the study: there is a difference in effect between progressive relaxation exercises and autogenic relaxation on the results of free-throw shooting (Fvalue = 8.471 > Ftable = 3.59), progressive relaxation exercises are better than autogenic relaxation exercises, there is a difference in effect between high and low category concentrations on free-throw shooting results, (Fvalue = 8,471 > Ftable = 3.59), athletes with high category concentrations have more influence on free-throw shooting results, compared to athletes with low category concentrations, there is an interaction between relaxation training methods, and concentration on the results of free-throw shooting, (Fvalue = 5.882 > Ftable = 3.59). Conclusions from the results of this study are there is a difference in the effect between relaxation exercises (progressive and autogenic) on the results of free-throw shooting on the Integrated Islamic Junior High School Bina Amal basketball team. There is a difference of effect between high and low category concentrations on free-throw shooting on the Bina Amal Integrated Islamic Junior High School basketball team. There is an interaction between relaxation training methods and concentration on free-throw shooting on the Integrated Islamic Junior High School Bina Amal basketball team. This research suggests that the results of the study of the effects of progressive relaxation exercises, and concentration on the results of free-throw shooting can be continued by researchers and other sports enthusiasts with different problem variables so that the research results are more complex and in-depth.